2017
DOI: 10.1504/ier.2017.084193
|View full text |Cite
|
Sign up to set email alerts
|

Urban air pollution control: selection of trees for ecological monitoring using anticipated performance indices in a medium-size urban area in Southwest Nigeria

Abstract: Abstract:The study assessed the biochemical parameters, sensitivity and tolerance levels to air pollution of the leaves of selected tree species along major roads in Ile-Ife in order to determine the tree species that will be most suitable in developing greenbelts along roadsides. The air pollution tolerance index (APTI) ranged from 8.5 to 13.9 for the entire tree species studied with Gmelina arborea, Polyalthia longifolia, Mangifera indica, Terminalia catappa and Tectona grandis having the highest during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 8 publications
3
5
0
Order By: Relevance
“…On comparing the previous studies with the present study as shown in Table 5, it was observed that S2 has showed higher pH value than reported by Singh et al [26] and S6 has reported higher pH values than reported by Adamsab et al [30], Anake et al [31], Ogunkunle et al [32], Ogunrotimi et al [33].…”
Section: Leaf Extract Phsupporting
confidence: 71%
See 3 more Smart Citations
“…On comparing the previous studies with the present study as shown in Table 5, it was observed that S2 has showed higher pH value than reported by Singh et al [26] and S6 has reported higher pH values than reported by Adamsab et al [30], Anake et al [31], Ogunkunle et al [32], Ogunrotimi et al [33].…”
Section: Leaf Extract Phsupporting
confidence: 71%
“…The comparative data of previous and present study shown in Table 7 revealed that the APTI values observed in the present study were higher for -S1 sample than reported by Das et al [2], Banerjee et al [38], S2 sample than reported by Krishnaveni and Lavanya [40], S6 sample than reported by Adamsab et al [30], Anake et al [31], Ogunkunle et al [32], Ogunrotimi et al [33], Krishnaveni et al [43], Govindaraju et al [44], Paulsamy and Senthilkumar [45].…”
Section: Aptisupporting
confidence: 56%
See 2 more Smart Citations
“…Plant species such as trees, shrubs and herbs act as bioindicators (detectors) and biomonitors of pollution in the environment (Ogunrotimi et al, 2017; Diener & Mudu, 2021). ).…”
Section: Discussionmentioning
confidence: 99%